Techno economic analysis of PETSS (Pipeline energy transport and storage system) - Alhazaimeh, S.; Al Durra, A.; Muyeen, S.M. (2018)
© 2018 IEEE Electrical energy is the most utilized source of energy nowadays; it is essential for the well-being of humans. The proposed PETSS system offers a novel approach for energy transfer and storage utilizing the gas pipelines. The new proposed systems will be converting the electricity from renewable energy to potential energy in the form of pressure. The system dynamics is designed, analyzed and optimized using TRNSYS and MATLAB. Moreover, the system economical value is compared to existing electrical energy transportation and storage systems. The results yielded a promising result in terms of the payback period over the alternative systems.